Specification and English Tenses - Dalimunthe, Gilang Luthfie; Pratama, Ahmad Yudha; Aini, Nur; Sabillah, Dinda Salsa; Lubis, Yani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The abstract in the English version must be written with fulfill the rules of good English writing for abstracts in scientific papers. The sentences in the abstract must be written in sentence type (tenses) are appropriate .Therefore, the researcher uses Report Text material specifically about student experiences, so there are four students who will be observed by the researcher. The research method used is a descriptive method or what is usually called a qualitative method. And qualitative data will be conveyed by observing students' handwriting. Based on the research results, it can be concluded that there are two types of tenses used in writing abstracts in English; simple present tense for writing "background" and "conclusion", and simple past tense for "goals", "methods", and "results". To minimize errors in using tenses, it would be better if each journal attached a file about the use of tenses in each abstract component.